Do 'difficult to identify' pulmonary vein connections explain continuing high recurrence rates after atrial fibrillation ablation?. (25th February 2019) - García-Bolao, Ignacio; Ballesteros, Gabriel; Ramos Ardanaz, Pablo; Vives, Enrique; Neglia, Renzo; Menéndez, Diego; Erkiaga Aio, Ane; de la Fuente, Ana
Abstract: Despite the emerging technical evolution of the last two decades, the primary success rate of single-procedure pulmonary vein isolation (PVI), the cornerstone for any atrial fibrillation ablation procedure, is highly variable ranging from 53% to 92%. The recent development of ultra-high-density electroanatomic mapping systems, capable of acquiring and annotating multiple electrograms, with high spatiotemporal precision, which are processed by automated algorithms to generate activation and substrate maps to support and guide ablation procedures, has opened a new stage in cardiac electrophysiology. In this article, we review the existing evidence on the utility of high-density mapping on catheter-based PVI, the possibility to detect pulmonary vein potentials that remain undetected when using a standard approach and its potential relevance to the clinical outcome, and how this new technology is providing novel pathophysiological insights on complete PVI and atrial fibrillation ablation outcomes.